Method for measuring intensity of inhomogeneous electrical fields by average value - S. V. Biryukov; L. V. Tyukina; A. V. Tyukin (Омский научный вестник)
Measurement and control of the intensity levels of inhomogeneous electric fields with high accuracy is quite a difficult task. The solution to this problem is connected both with the development of new sensors and methods for measuring the electric field strength. The creation of new high-precision electrical induction sensors has exhausted its capabilities at the current level of technology and technology. Therefore, new ideas are needed for solving the problems of high-precision measurement of the electric field strength. One of these ways is the development of new measurement methods. Existing measurement methods characterized by the complexity of the measurement processes, suitability in some cases, and unsuitability in others, do not provide the desired metrological characteristics. Therefore, the work related to the development of methods for measuring the intensity of inhomogeneous electric fields does not stand still, and is relevant. The aim of the study is to create a new method for measuring the strength of electric fields using known sensors, which makes it possible to significantly reduce the error in measuring inhomogeneous electric fields. The idea of constructing a new measurement method is formed. The idea of the method is that in the presence of two physical quantities measured with different sign values of the error, the average value of the physical quantity will always be closer to the true value. Based on this, a new method for measuring the intensity of inhomogeneous electric fields is proposed, associated only with the original measurement process. The measurement method id named «Average value method» (MSZ). The estimation of the error of this method shows a decrease in the measurement error to +5 % with the full spatial measurement range 0a1. Using the «Average value method» it is possible to achieve a significant increase in the accuracy of measuring the strength of inhomogeneous electric fields in a wide spatial range of measurements in comparison with known methods.